Determinan Penyerapan Tenaga Kerja Di Provinsi Jawa Timur - Evie Silfiana (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2023)
Problems that have not been resolved so far in Indonesia are related to employment. The increasing number of people looking for work is not proportional to the number of available jobs. This study aims to analyze the determinants of employment in East Java Province by using three independent variables, namely domestic investment, provincial minimum wage and number of industries. This study uses time series data with a period of 31 years, namely from 1990 to 2020. The method used is multiple linear regression. The results of the study show that PMDN investment, the provincial minimum wage and the number of industries have a significant influence on employment in East Java Province.